PERCEPTIONS OF BUILDERS AND FOREMEN ON SKILLS IMPROVEMENT NEEDS OF CRAFTSMEN IN CONSTRUCTION INDUSTRIES IN BAUCHI STATE, NIGERIA - Karfe, Roseline Yusuf; IdrisAbubakar Mohammed; Abdullahi Mohammed Hassan, (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2021)
This study was carried out to determine the Perceptions of Builders and foreman on skills improvement needs of Craftsmen in Construction Industries in Bauchi State, Nigeria. A descriptive survey research design was adopted for the study. The target population for the study was 61 respondents made up of 34 Builders and 27 Foremen in the Construction Industries. A 63 items structured questionnaire was used for data collection. The instrument was validated by three experts and Cronbach Alfa statistic was used to ascertain the extent of sameness of the items and a reliability coefficient of 0.824 was obtained. Data was collected and analyzed using a statistical package for social science (SPSS Version 22), weighted mean, standard deviation, and Improvement Need Index (INI) was used to answer the research questions while z-test statistic was used to test the null hypotheses. The findings of this study revealed that the whole 50 skills items were required, 22 out of 50 skills items were not possessed and 48 out of 50 skills items were the skills gap. It was therefore recommended amongst others that the construction industries should utilize the identified skills gap that exists to sponsorship their craftsmen for a re-training program in order to improve their skills deficiencies.